Physical origin of trench formation in ge/si(100) islands - Sonnet, Philippe; Kelires, Pantelis C. (My University, 2004)
The physical origin of trench formation in Ge/Si (100) islands was discussed using Monte Carlo simulations. The stress evolution as the island grows layer by layer indicted that a trench was most likely being formed halfway during growth. It was found that the primary driving force for this phenomenon was the reduction of the concentrated stress below the edges of the islands. Analysis shows that once the trench is formed subsequent intermixing through it is enhanced and nearly compensates for the stress in the island.
Keywords: Silicon; Wetting; Germanium